Environmental Pollutants PM2.5, PM10, Nitrogen Dioxide (NO2), and Ozone (O3) Association with the Incidence of Monkeypox Cases in European Countries - Sultan Ayoub Meo; Sara A. Alqahtani; Anusha Sultan Meo; Joud Mohammed Alkhalifah; Thamir Al-Khlaiwi; David C. Klonoff (Journal of Tropical Medicine, 2023)
Background. Monkeypox, also known as monkeypox disease, is caused by the monkeypox virus (MPXV), which is a zoonotic infection. The swift spread of human monkeypox cases has caused an alarming situation worldwide. This novel study aimed to investigate the association of particulate matter air pollutants PM2.5, PM10, Nitrogen dioxide (NO2), and Ozone (O3) on the incidence of monkeypox cases from May 1, 2022, to July 15, 2022. Methods. The data on air pollutants PM2.5, PM10, NO2, and O3 and monkeypox cases were recorded from the date of occurrence of the first case of monkeypox in the United Kingdom, Spain, France, Germany, Italy, the Netherlands, Switzerland, and Portugal from May 1, 2022, to July 15, 2022. The daily concentrations of PM2.5, PM10, NO2, and O3 were recorded from the metrological website “Air Quality Index-AQI,” and daily human monkeypox cases were recorded from the official website of “Our World in Data.” The mean values along with simple, multiple, and Spearman Rho correlations were performed to investigate the relationship and strength of association between the concentrations of air pollutants and cases of monkeypox. Results. The environmental pollutants PM2.5, PM10, NO2, and O3 were positively associated with monkeypox cases in the United Kingdom, Spain, France, Germany, Italy, the Netherlands, Switzerland, and Portugal. The analysis further revealed that for each 10-unit increase in PM2.5, PM10, and NO2, levels, the number of monkeypox cases was significantly augmented by 29.6%, 9.7%, 13%, and 80.6%, respectively. Conclusions. Environmental pollutants PM2.5, PM10, NO2, and O3 have been positively linked to the number of daily monkeypox cases in European countries. Environmental pollution is a risk factor for the increasing incidence of monkeypox daily cases. The regional and international authorities must implement policies to curtail air pollution to combat the cases of monkeypox in European countries and worldwide.